Social interaction, support preferences, and the use of wearable health trackers - Pennington, Natalie; Dam, Linda (Frontiers in Communication, 2023)
Drawing on uses and gratifications theory, social cognitive theory, and related work, this research assessed how social factors relate to reported weekly use and behavioral intentions toward the use of wearable health trackers (WHT). Through two studies we surveyed current users of WHT, including smartwatches, to better understand what factors encouraged engagement. Study One (N = 333) consisted of a college student sample. Results suggested that connection, social comparison, and one's comfort with seeking support predicted weekly use, while need for support was a negative predictor of device use. In terms of behavioral intentions, connection and one's comfort with seeking support remained positive predictors. Study Two (N = 319) was conducted through an online panel from Prolific. In this case, only one's comfort with seeking support predicted weekly use, while one's comfort with seeking support and social sharing both predicted behavioral intentions. Additional analysis in Study Two comparing users of dedicated WHT and smartwatches also found differences in terms of behavioral intentions and social sharing. Collectively, the two studies offer insight into what social factors contribute to the use of WHT.